Pengaruh Brand Image dan Kualitas Layanan terhadap Keputusan Orang Tua dalam memilih Jasa Pendidikan di SD Labschool UNESA 1 Surabaya - Fadhilah, Lina Amalia Nur; Sudarwanto, Tri (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This study aims to determine the influence of brand image and service quality on parents' decisions in choosing a school for their children. The research uses a quantitative approach with 49 respondents, who are the guardians of first-grade students at SD Labschool UNESA 1 Surabaya, utilizing the total sampling method. Data were collected through questionnaires, documentation, and supporting school documents. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, as well as F-tests (simultaneous) and t-tests (partial). The results showed that partially, brand image has a positive and significant influence on parents' decisions; the more attractive and high-quality the school's brand image, the more parents choose the school. Service quality also has a positive and significant impact; the better the services offered, the more parents select this school. Simultaneously, these two variables have a positive and significant impact on parents' decisions, mutually supporting the decision-making process. In conclusion, improving the quality of these two aspects will enhance parents' confidence and decision to choose SD Labschool UNESA 1 Surabaya as the right educational institution for their children.